DoE Experimental design in HPLC separation of pharmaceuticals; a review: DoE in HPLC drug analysis - Stojanović, Jevrem; Krmar, Jovana; Protić, Ana; Svrkota, Bojana; Djajić, Nevena; Otašević, Biljana (Archives of Pharmacy, 2021)
Design of Experiments (DoE) is an indispensable tool in contemporary drug analysis as it simultaneously balances a number of chromatographic parameters to ensure optimal separation in High Pressure Liquid Chromatography (HPLC). This manuscript briefly outlines the theoretical background of the DoE and provides step-by-step instruction for its implementation in HPLC pharmaceutical practice. It particularly discusses the classification of various design types and their possibilities to rationalize the different stages of HPLC method development workflow, such as the selection of the most influential factors, factors optimization and assessment of the method robustness. Additionally, the application of the DoE-based Analytical Quality by Design (AQbD) concept in the LC method development has been summarized. Recent achievements in the use of DoE in the development of stability-indicating LC and hyphenated LC-MS methods have also been briefly reported. Performing of Quantitative structure retention relationship (QSRR) study enhanced with DoE-based data collection was recomended as a future perspective in description of retention in HPLC system.